Synergy between melamine cyanurate, melamine polyphosphate and aluminum diethylphosphinate in flame retarded thermoplastic polyurethane. (April 2019) - Sut, Aleksandra; Metzsch-Zilligen, Elke; Großhauser, Michael; Pfaendner, Rudolf; Schartel, Bernhard
Abstract: The multicomponent flame retardant system of melamine polyphosphate (MPP), melamine cyanurate (MC) and aluminum diethylphosphinate (AlPi) is proposed and investigated for thermoplastic polyurethane (TPU). The synergy between those additives and the resulting superior fire performance are discussed. Systematically varied sets of flame retarded TPU with various MPP/MC/AlPi ratios were investigated in terms of fire behavior, pyrolysis products and mechanical properties. The total amount of the additives was always 30 wt.-%. Further, the influence of various AlPi concentrations was investigated. The optimal MPP:MC ratio was determined while keeping the amount of AlPi constant. The combination of 8 wt.-% MPP, 12 wt.-% MC and 10 wt.-% is proposed as the most promising halogen free flame retardant formulation for TPU, because it yielded a reduction in PHRR from 2660 kW/m 2 (TPU) to 452 kW/m 2 and enabled V-0 classification in the UL 94 test. Combinations of MPP and MC as well a high concentration of AlPi are beneficial for the mechanical properties e.g. tensile strength and elongation at break of the formulations and could be a strong competitor to commercial flame retarded TPUs. Highlights: Halogen-free multicomponent flame retarded system was proposed as a promising approach for thermoplastic polyurethane (TPU). Systematically varied melamine polyphosphate (MPP)/melamine cyanurate (MC)/aluminum diethylphosphinate (AlPi) ratio was investigated. The proportions of the additives had a significant influence on the performance and synergistic interaction. The desired properties were adjusted without increasing the total amount or the type of the flame retardants. Once the optimal composition was reached, both the fire behavior and mechanical properties were improved.